Different active exogenous carbons improve the yield and quality of roses by shaping different bacterial communities - Li, Shixiong; Peng, Yuanyang; Li, Manying; Li, Xin; Li, Haoyang; Dabu, Xilatu; Yang, Yun (Frontiers in Microbiology, 2025)
The application of exogenous organic carbon represents a significant strategy for enhancing soil fertility and promoting sustainable agricultural development. This approach modifies the physicochemical properties of soil and influences microbial community structures, consequently improving crop yield and quality. Nevertheless, the mechanisms underlying microbial community responses to various forms of active exogenous organic carbon remain poorly understood and require further investigation. A 1-year follow-up experiment was conducted to examine the effects of different carbon sources on the yield and quality of cut roses, along with the characteristics of the soil bacterial community. The results indicated that applying organic fertiliser and biochar significantly enhanced the productivity of cut roses, demonstrating a sustained growth-promoting effect. Organic fertiliser provides more active, readily oxidisable organic carbon to the soil compared to biochar. In contrast, biochar supplies stable organic carbon, including inert organic carbon that is difficult to oxidise, firm organic carbon (FOC), and total inert organic carbon, which has a high degree of humification that significantly exceeds that of organic fertiliser. The application of biochar and organic fertiliser not only altered the abundance, diversity, and composition of the rhizosphere microbial community but also enriched beneficial microorganisms. Redundancy analysis results indicated that FOC, available phosphorus, and soil organic matter were the primary factors influencing the bacterial community. The results of this study demonstrated that exogenous organic carbon exerted positive and indirect effects on crop yield by influencing soil properties and bacterial communities. These findings provide novel evidence supporting the rational application of biochar and organic fertilisers as a means to promote agricultural sustainability in red soil regions.